Comparative proteomics of biofilm development in Pseudoalteromonas tunicata discovers a distinct family of Ca2+-dependent adhesins - Sura Ali; Alexander Stavropoulos; Benjamin Jenkins; Sadie Graves; Atiyeh Ahmadi; Vania Marzbanrad; Geoffrey Che; Jiujun Cheng; Huagang Tan; Xin Wei; Suhelen Egan; Brian Ingalls; et al. (mBio)
ABSTRACT The marine bacterium, Pseudoalteromonas tunicata, is a useful model for studying biofilm development due to its ability to colonize and form biofilms on a variety of marine and eukaryotic host-associated surfaces. However, the pathways responsible for P. tunicata biofilm formation are not fully understood, in part due to a lack of functional information for a large proportion of its proteome. We used comparative shotgun proteomics to explore P. tunicata biofilm development from the planktonic phase throughout early, middle, and late biofilm stages. A total of 248 biofilm-associated proteins were identified, including many hypothetical proteins, as well as previously known P. tunicata biofilm-related proteins, such as the autocidal enzyme AlpP, violacein proteins, S-layer protein SLR4, and various pili proteins. We further investigated the top identified biofilm-associated protein, a previously uncharacterized 1,600-amino acid protein (EAR30327), which we designate as “BapP.” Based on AlphaFold modeling and genomic context analysis, we predicted BapP as a distinct Ca2+-dependent biofilm adhesin. Consistent with this prediction, a ΔbapP knockout mutant was defective in forming both pellicle- and surface-associated biofilms and rescued by re-insertion of bapP into the genome. Similar to the mechanisms of RTX Bap-like adhesins, BapP-mediated biofilm formation was influenced by Ca2+ levels, and BapP is potentially exported by a Type 1 secretion system. Ultimately, our work not only provides a useful proteomic data set for studying biofilm development in an ecologically relevant organism but also adds to our knowledge of bacterial adhesin diversity, emphasizing Bap-like proteins as widespread determinants of biofilm formation in bacteria.IMPORTANCEUnderstanding how bacteria form biofilms is essential because biofilms play a crucial role in bacterial survival and interaction with their environments. The marine bacterium Pseudoalteromonas tunicata is a valuable model for studying biofilm formation, as it colonizes diverse marine surfaces and host organisms. By identifying proteins involved in biofilm development, our study sheds light on the specific proteins that help P. tunicata transition from a free-swimming state to a stable biofilm. This work highlights the role of a large, calcium-dependent protein, BapP, which we found to be essential for biofilm stability and structure. This protein and hundreds of others identified provide new insights into bacterial adhesion mechanisms, expanding our understanding of biofilm formation in marine environments and potentially informing broader studies on biofilm-related processes in other bacteria.